A Review of Culture-Based Learning at Primary Level In Indonesia - Yuyun Elizabeth Patras; Ai Juliani; Nina Nurhasanah; Arifin Maksum; Rais Hidayat (STAI Hubbulwathan Duri, 2023)
This study aims to present a review of culture-based learning in primary school. The results of research have been found in several articles related to the implementation of culturally responsive teaching (CRT) or culture based learning. The findings in these articles were then used as a basis for formulating a new way of discussing culture-based learning (CRT) at the primary school level. The methodology used in this study is a literature search of articles in both Indonesian and English in 2018-2021 sourced from Google Scholar, Scopus.com, and Garuda search sites using the keywords “implementation of culturally responsive teaching”, “implementation of culture-based learning